2016
DOI: 10.3847/1538-4357/833/1/112
|View full text |Cite
|
Sign up to set email alerts
|

GAS FRACTION AND DEPLETION TIME OF MASSIVE STAR-FORMING GALAXIES AT z ∼ 3.2: NO CHANGE IN GLOBAL STAR FORMATION PROCESS OUT TO z > 3

Abstract: The observed evolution of the gas fraction and its associated depletion time in main-sequence (MS) galaxies provides insights on how star formation proceeds over cosmic time. We report ALMA detections of the rest-frame ∼300 μm continuum observed at 240 GHz for 45 massive (), i.e., MS, galaxies at » z 3.2 in the COSMOS field. From an empirical calibration between cold neutral, i.e., molecular and atomic, gas mass M gas and monochromatic (rest-frame) infrared luminosity, the gas mass for this sample is derived. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
149
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(169 citation statements)
references
References 65 publications
(182 reference statements)
20
149
0
Order By: Relevance
“…By restricting galaxies in PHIBBS-I, which results in only sevengalaxies for comparison, we find that the average gas fraction does not differ (á ñ -f gas,PHIBBS I,MS =0.49±0.05;bottom of Figure 10). Other studies on the main-sequence galaxies have revealed similar results (e.g., Magdis et al 2012;Saintonge et al 2013;Sargent et al 2014;Scoville et al 2014;S16;Schinnerer et al 2016). ALESS SMGs on the massive main sequence at < < z 2 3 (total number of 13) appear to have a slightly higher mean value (á ñ f gas =0.64±0.07; Figure 10 top) but is nevertheless consistent within an error.…”
Section: Gas Fractionsupporting
confidence: 63%
See 1 more Smart Citation
“…By restricting galaxies in PHIBBS-I, which results in only sevengalaxies for comparison, we find that the average gas fraction does not differ (á ñ -f gas,PHIBBS I,MS =0.49±0.05;bottom of Figure 10). Other studies on the main-sequence galaxies have revealed similar results (e.g., Magdis et al 2012;Saintonge et al 2013;Sargent et al 2014;Scoville et al 2014;S16;Schinnerer et al 2016). ALESS SMGs on the massive main sequence at < < z 2 3 (total number of 13) appear to have a slightly higher mean value (á ñ f gas =0.64±0.07; Figure 10 top) but is nevertheless consistent within an error.…”
Section: Gas Fractionsupporting
confidence: 63%
“…With the advent of large surveys revealing the gas content of star-forming galaxies, the evolution of sSFR appears to be caused by the higher gas fraction ( star, at least on the main sequence. Furthermore, the higher M gas appears to mimic the higher gas supply rate (e.g., Magdis et al 2012;Saintonge et al 2013;Tacconi et al 2013;Sargent et al 2014;Genzel et al 2015, hereafter G15;Scoville et al 2014Scoville et al , 2016Scoville et al , hereafter S16, 2017Schinnerer et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Our new analysis reveals a large, highly obscured stellar mass, similar to the most massive and extreme SMGs during the peak of star formation (e.g., Hainline et al 2011;Ma et al 2015;Schinnerer et al 2016;Miettinen et al 2017;Nayyeri et al 2017). However, as already discussed in Conley et al (2011) andWardlow et al (2013), HLock01-R has a moderately low q IR =1.8±0.4 (which is the logarithmic ratio of L IR and the rest-frame 1.4 GHz flux density), compared with the mean value for HerMES sources (q IR =2.40±0.12; Ivison et al 2010a).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Also, Scoville et al (2017) and Schinnerer et al (2016), were able to place constraints on the gas masses of individual galaxies up to z = 4, using single band measurements of the dust emission flux on the Rayleigh-Jeans side of their SED. Finally, Magdis et al (2012a), and Tan et al (2014), presented CO observations, and therefore M H 2 estimates for a couple of z = 3 − 4 Lyman Break Galaxies (LBGs).…”
Section: Introductionmentioning
confidence: 99%